2021
DOI: 10.1101/2021.01.20.427412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential requirement of NPHP1 for compartmentalized protein localization during photoreceptor outer segment development and maintenance

Abstract: Nephrocystin (NPHP1) is a ciliary transition zone protein and its ablation causes nephronophthisis (NPHP) with partially penetrant retinal dystrophy. However, the precise requirements of NPHP1 in photoreceptors are not well understood. Here, we characterize retinal degeneration in a mouse model of NPHP1 and show that NPHP1 is required to prevent infiltration of inner segment plasma membrane proteins into the outer segment during the photoreceptor maturation. We demonstrate that Nphp1 gene-trap mutant mice, whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…15,42 In Nphp1 gene-trap mutant mice, which are likely hypomorphs due to the production of a small quantity of functional messenger RNAs, photoreceptors fail to develop normal outer segments because of an impaired intraflagellar transport. 16,17,19 Such abnormal photoreceptor outer segments are likely the structural correlate for the consistent human phenotype on OCT imaging that is already present in very mild disease (see earlier). Over time, the mouse model develops photoreceptor atrophy, which again finds its OCTbased correlate in thinning of the outer retina in humans.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…15,42 In Nphp1 gene-trap mutant mice, which are likely hypomorphs due to the production of a small quantity of functional messenger RNAs, photoreceptors fail to develop normal outer segments because of an impaired intraflagellar transport. 16,17,19 Such abnormal photoreceptor outer segments are likely the structural correlate for the consistent human phenotype on OCT imaging that is already present in very mild disease (see earlier). Over time, the mouse model develops photoreceptor atrophy, which again finds its OCTbased correlate in thinning of the outer retina in humans.…”
Section: Discussionmentioning
confidence: 81%
“…[49][50][51][52][53] The presence of a heterozygous variant in Cep290 has been reported to result in more rapid retinal degeneration in mice lacking Rpgr, and variants in Ahi1/AHI1 have been reported to modify Nphp1-(in mice) as well as CEP290-related retinal degeneration (in humans). [52][53][54] Recently, Datta et al 19 demonstrated that a reduced gene dose of Cep290 exacerbates protein mislocalization and retinal degeneration in Nphp1 mutant mice. Furthermore, it has been shown that CEP290 variants can modify the extrarenal symptoms in patients with NPHP1 mutations, 45 a phenomenon also seen in other ciliopathies such as Bardet-Biedl syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal sections were stained with rabbit anti-OPN1MW polyclonal antibody (EMD Millipore AB5405) and rabbit anti-GNAT2 polyclonal antibody (Abcam ab97501). Methods to perform immunofluorescence stainings are as previously described (Datta et al, 2021;Datta et al, 2019;Datta et al, 2020). Transmission electron microscopy was performed as described previously (Hsu et al, 2017).…”
Section: Microscopic Anatomymentioning
confidence: 99%